NILAI-NILAI EKONOMI ISLAM DALAM SISTEM PENGGAJIAN KARYAWAN (STUDI PADA PUSAT BEKAM RUQYAH CABANG DUKUH ZAMRUD KOTA BEKASI) - Mufid Habib Mustofa; Abdul Samad Kelsaba (Institut Bisnis Muhammadiyah Bekasi, 2022)
Islam governs all aspects of this universe, from the smallest to the biggest. Islam also regulates the concept of payroll employees well without decorating other parties. This research will discuss muamalah worship in the theme of Islamic Economic Values in the Employee Payroll System at the Ruqyah Cupping Center, Dukuh Emerald Branch, Bekasi City. Using primary data, this research will explore all kinds of realities and problems that occur in employee payroll based on Islamic economic values. The results of this study show that with the rules set by Islam, this life will follow the haq flow to go to maslahatan in realizing falah (happiness). One of the indicators that is the subject of discussion is that in preaching, it does not have to be with the material or ability that is possessed. As conclusion in this study, one of the categories is to preach treasure on the haq path to the happiness of the world and the hereafter.